Management Control System Analysis in Improving Employee Performance at Indomaret Selamat Kataren Branch - Manik, Citra Wulandari; Krisnawati Silaban; Mahlina Putri Manurung; Sienny (Outline Publisher, 2023)
Management is a process of cooperation between two or more people to achieve the goals that have been set. Indomaret minimarket fishing branch is a private company engaged in buying and selling. Shares are one of the assets of the Indomaret Minimarket company. or loss. So it is necessary how to manage and organize this Indomaret branch of the fishing mini market. The method used in this study is a qualitative method. The problems raised in this research report are how the management control system is implemented in Indomaret, what are the problems in running management at Indomaret, is the control system management at Indomaret appropriate. The stages of this research are divided into the planning stage, the observation stage and the questionnaire filling stage.